1975
DOI: 10.1007/bf00201181
|View full text |Cite
|
Sign up to set email alerts
|

Insulin in post-mortem blood

Abstract: In 29 cases of sudden death the insulin concentration in blood from the right heart and the femoral vein was determined by a radioimmunological method. The concentrations in the femoral venous blood were below 60 muU/ml serum (mean 23 muU/ml), i.e. in the same order of magnitude as in living persons. In right heart blood the insulin values were about 10 times higher, probably due to post-mortal diffusion of insulin via the portal vein. In suspected hyperinsulinism the measurements should therefore be made on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In post mortem insulin assays the insulin values measured in right heart blood were about ten times higher probably due to post-mortal diffusion of insulin via the portal vein [67,128]. The measurements should therefore be made on peripheral venous (femoral or iliac) blood [25]. Fig.…”
Section: Analytical Interferences and Sample Storage For The Peptidesmentioning
confidence: 98%
See 2 more Smart Citations
“…In post mortem insulin assays the insulin values measured in right heart blood were about ten times higher probably due to post-mortal diffusion of insulin via the portal vein [67,128]. The measurements should therefore be made on peripheral venous (femoral or iliac) blood [25]. Fig.…”
Section: Analytical Interferences and Sample Storage For The Peptidesmentioning
confidence: 98%
“…Using non-compartmental analysis in a case of human insulin intoxication in a type 1 diabetic, Shibutani and Ogawa [23] found an elimination half-life of 6.2 h. In another case of insulin poisoning in a type 1 diabetic patient, Fasching [24] identified a slow biphasic decrease with half-lives of 4 and 10 h for the two successive phases, respectively. Forensic scientists reported that serum insulin concentration in corpses varies significantly amongst individuals [25]. Iwase et al [26] said that insulin level may decrease after death.…”
Section: Human Insulin Synthetic Insulin Analogues C-peptide and Prmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently. significant progress has been made in the study of the ATP-binding site by using [71.____ ~~ vanadate, which is considered a good structural analogue of phosphate [14]. The S1 95-kDa heavy chain is specifically cleaved by near-ultraviolet irradiation in the presence of vanadate at sites 23-kDa and 74-kDa from the N-terminus, and regions in the vicinity of these cleavage sites were assumed to be the phosphate-binding sites of S1 [15, 161.…”
mentioning
confidence: 99%
“…____ ~~ vanadate, which is considered a good structural analogue of phosphate [14]. The S1 95-kDa heavy chain is specifically cleaved by near-ultraviolet irradiation in the presence of vanadate at sites 23-kDa and 74-kDa from the N-terminus, and regions in the vicinity of these cleavage sites were assumed to be the phosphate-binding sites of S1 [15, 161. The cleavage site at 23 kDa from the N-terminus was localized at Serl80 [17], supporting the conclusions of the homology analysis, viz.…”
mentioning
confidence: 99%